Introduction of water filtration using PVC pipe to be waterworth for the community - Dandi Febrian; Pristiyono Pristiyono; Abdul Halim (Universitas Muhammadiyah Magelang, 2022)
This community empowerment program focuses on how to prevent the spread of Covid-19 by using simple and inexpensive equipment to solve the problem of clean water availability. The objective of this program is to train the residents of Kampung Baru Village about the strategy of providing clean water through PVC water filtration. Socialization, training, and mentoring are the methods of community empowerment used in Kampung Baru Village, Bilah Barat District, Labuhanbatu Regency. The public's knowledge of how to produce clean water with a filter increased as a result of the program implementation, as well as the community was able to assemble a water filter using PVC pipe, and the water filter trial was successfully completed.